Estudo de compostos cerâmicos para utilização em coatings de alta emissividade - Campiteli, Ricardo Guimarães (Universidade Federal de São Carlos, 2016)
The constant search for means to reduce the energetic consumption motivates the use of high emissivity ceramic coatings in many high temperature applications. Its use aims to increase heat transfer efficiency by radiation from substrates on which coatings are applied, reducing the emission of gases that contribute to global warming by saving energy in heating processes. They are composed by refractory components and high emissivity materials such as cerium oxide, chromium (III) oxide, boron carbide and others with scarce availability or low commercial viability. The objective of this study is to improve knowledge in the compounds of high melting point that have high emissivity, seeking alternatives to more abundant and greater efficiency in their use in ceramic coatings compositions. For this purpose were evaluated different ceramic compounds in the composition of these high emissivity coatings. To verify the heat transfer efficiency was analyzed the coated surfaces and its temperature maintenance in substrates with and without application of coating, by an indirect method of measuring the emissivity. This method basically consists in compare the emissivity from the different coated surfaces with various coating compositions made from viable emissivity agents, using infrared temperature measurement. Also its microstructure and the chemical analysis were evaluated. The use of iron chromite achieved a promising result elevating the surface emissivity about 8% in relation to a coating composition without any emissive agent.
Study of ceramic compounds for high emissivity coatings
Keywords: Emissividade; Coatings cerâmicos; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA